Two new freshwater blennies from the Eastern Mediterranean basin (Teleostei: Blenniidae) - Yoğurtçuoğlu, Baran; Kaya, Cüneyt; Atalay, Mustafa Altuğ; Ekmekçi̇ Fitnat Güler; Freyhof, Jörg (Zootaxa, 2023)
Two new species of Salariopsis are described from the Eastern Mediterranean basin. Salariopsis burcuae, new species, from the Bay of Antalya east to the Jordan, is characterised by having a short cirrus, usually not overlapping the 9th circum-orbital sensory pore, and many tiny black dots on the cheek not organised in rows or bands. The new species shows a 4.1% K2P sequence divergence on the cytochrome-c-oxidase subunit 1 (COI) barcoding region from its closest relative, S. fluviatilis. Salariopsis renatorum, new species, from the upper Ceyhan drainage and a coastal stream in Arsuz, is distinguished by having an unbranched supraocular tentacle, black lateral line pores, a short snout, and no black dots on the upper part of the flank and on the cheek. It is also distinguished from its geographically closest congener, S. burcuae, by a molecular distance of 8.8% K2P in its COI barcode region.